Composite rock slice and preparation method thereof
By using components such as high elasticity and low back viscosity resin to prepare composite rock flakes with a thickness of 40-100μm, the problems of thicker thickness and poor flexibility are solved, thinner layering and simulation degree are achieved, coating volume is reduced, and cost savings are saved.
Patent Information
- Application Number
- CN202510393925.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-08-08
AI Technical Summary
The existing composite rock flakes have thicker thickness and poor flexibility and compatibility, resulting in large amounts of coating during spraying, wasted costs and insufficient simulation.
Composite rock flakes with a thickness of 40-100μm are prepared by using high elastic and low viscosity resin, coupling agent, anti-adhesive agent and mold release agent to enhance flexibility and compatibility and reduce the coating amount.
The thin layering of composite rock flakes is achieved, the simulation degree and customer experience are improved, the coating volume is reduced, and the cost is saved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new building materials, in particular to a composite rock slice and a preparation method thereof. Background Art
[0002] Early real stone paints were highly sought after for their sandy texture, hardness, and crack resistance, replacing most common exterior paints. Later, because the smaller colored sand particles in real stone paints couldn't replicate granite patterns, composite rock flakes were added to further enhance the fidelity of the granite-like decorative effect. The greater the area of composite rock flakes per spray area, the more realistic the effect. However, because standard composite rock flakes are thick and hard, they lack compatibility with smaller nozzles, requiring larger nozzles. This results in excessive coating application, requiring 4-5 kg. The flakes don't blend into the coating, causing them to warp. Therefore, composite rock flakes need to be as thin, flexible, and well-compatible as possible. For the same pattern ratio, thinner flakes can use significantly less weight. Because they are flexible, nozzles don't need to be larger, and the amount of stone-like paint applied doesn't need to be large. However, currently available composite rock flakes cannot be very thin, typically measuring 200-300 μm. Thinner thickness significantly reduces the flakes' durability, water resistance, and mechanical agitation resistance. When the film is too thin, it cannot be peeled off from the drying carrier due to coating fastness, adhesion, viscosity and electrostatic effects.
[0003] Document CN 110819155 A discloses an ultra-thin rock sheet with excellent adhesion resistance and easy demolding properties, and its preparation process. The raw materials include the following components by weight: 30-50 parts acrylic resin, 1-5 parts fluorocarbon resin, 0.001-0.01 parts cellulose, 0.02-0.1 parts cross-linking agent, 0.5-5 parts mold release agent, 30-60 parts filler, and 5-15 parts water. The ultra-thin rock sheet has a thickness of 30-70 μm. The composite rock sheet described in this document has poor flexibility and durability, and requires a large coating amount, resulting in waste.
[0004] Therefore, a new technical solution is needed to solve the above technical problems. Summary of the Invention
[0005] In order to solve the above problems, the present invention discloses a composite rock sheet and a preparation method thereof. Under the premise of ensuring coating fastness, adhesion, viscosity and electrostatic effect, the composite rock sheet is made into 40-100um, reducing the coating amount and saving costs.
[0006] The technical solution of the present invention is: the composite rock slices, the raw materials of which include the following components in parts by weight: 25-40 parts of high elasticity and low tack resin; Dispersant 0.1-0.5 parts; Wetting agent 0.1-0.5 parts; Coupling agent 0.02-0.1 parts; 0.05-5 parts of release agent; Anti-adhesive agent 0.01-0.1 part; Thickener 0.1 part -1 part; Filling powder 50-60 parts; 0.1-2 parts of water-based color paste; 5-15 parts water.
[0007] Preferably, the high elasticity and low tack resin refers to an acrylic emulsion, which is a type of acrylic emulsion having a micro-crosslinked structure by adding an appropriate amount of soft monomer to lower the Tg, i.e., the glass transition temperature, and forming ether bonds, bonds or amide groups through the interaction of special functional groups carried by the added functional monomers or oligomers, or forming C-C bonds of the macromolecular chain through the addition action between double bonds.
[0008] Preferably, the coupling agent is one or more of methyl silicate, silane coupling agent, isocyanate and polyamine.
[0009] Preferably, the release agent is one or more of methyl silicone oil, hydroxy silicone oil, phenyl silicone oil, amino silicone oil, mineral oil and alkyl oil.
[0010] Preferably, the antistatic agent is a complex of a quaternary ammonium salt cationic surfactant and a nonionic surfactant.
[0011] Preferably, the anti-sticking agent is one or more combinations of polytetrafluoroethylene powder, polyethylene wax, polypropylene wax and polyamide wax, and the filling powder is one or more of kaolin, calcium carbonate powder, titanium dioxide and talc.
[0012] Preferably, the wetting agent is one or more of anionic wetting agents and nonionic wetting agents.
[0013] Preferably, the thickener is one or more of hydroxyethyl cellulose, alkali-soluble thickener, associative thickener, and polyurethane thickener.
[0014] The preparation method of the composite rock slice comprises the following steps Step 1: Evenly disperse the formula and stir it into slurry, then evenly apply the slurry on the drying line base belt. The drying line base belt passes through a hot air circulation oven and is peeled off by a brush roller. Step 2: The dried coating layer is crushed by a crusher and then sieved by a screening machine to obtain flakes with a size of 1-10mm, which are packaged according to color and size. Step 3: Place the sheets in polyethylene plastic bags, and then place the polyethylene plastic bags in corrugated boxes for shipment.
[0015] Preferably, the drying temperature is 100-120 degrees, the wind speed is 0.5-2m / s, the thickness of the coating after drying is controlled at 40-70um, and the speed of the brush roller is 200-300 rpm.
[0016] The benefits of the present invention are: 1. The thickness of the product of the present invention is 40-100um, while the thickness of the previous rock slices was 200-300um. The surface area or the number of single rock slices after unfolding with the same weight of the present invention will increase by 4-5 times, thereby reducing the amount of rock slices used in the real stone paint and the coating amount of the real stone paint, saving costs.
[0017] 2. The shape of the composite rock slice product of the present invention is an irregular polygon with no repetition, which is closer to the crystal effect of the texture of granite itself, so that the simulation is more realistic, improving customer experience and increasing product sales.
[0018] 3. The present invention adopts a high-elasticity, low-rebound resin and a coupling agent to enhance the flexibility and firmness of the composite rock slices. The addition of an anti-adhesive agent, a release agent, and an antistatic agent solves the problem that the composite rock slices are too thin to be peeled off from the drying carrier. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Example 1
[0020] 35 parts of elastic methyl acrylate resin, 20 parts of kaolin, 25 parts of calcium carbonate powder, 5 parts of titanium dioxide, 0.3 parts of dispersant, 0.3 parts of wetting agent, 0.1 parts of silane coupling agent, 2 parts of methyl silicone oil, 0.1 parts of polytetrafluoroethylene powder, 0.005 parts of hydroxyethyl cellulose, 0.2 parts of anionic antistatic agent, 0.5 parts of defoaming agent, 0.1 parts of water-based color paste, 11.395 parts of water; The preparation method of the composite rock slice comprises the following steps Step 1: Evenly disperse the formula and stir it into slurry, and evenly apply the slurry on the drying line base belt. The drying line base belt passes through a hot air circulation oven with a drying temperature of 110 degrees and a wind speed of 1m / s. The thickness of the coating after drying is controlled at 50um, and the coating is peeled off by a brush roller with a speed of 250 rpm. Step 2: The dried coating layer is crushed by a crusher and then sieved by a screening machine to obtain 2mm flakes, which are packaged according to color and size. Step 3: Place the sheets in polyethylene plastic bags, and then place the polyethylene plastic bags in corrugated boxes for shipment. Example 2
[0021] 40 parts of elastic acrylic resin n-butyl grease, 10 parts of talc, 25 parts of light calcium carbonate powder, 10 parts of titanium dioxide, 0.3 parts of dispersant, 0.3 parts of wetting agent, 0.2 parts of polyamine, 4 parts of amino silicone oil, 0.2 parts of polyethylene wax, 0.2 parts of alkali swelling thickener, 0.3 parts of nonionic antistatic agent, 0.5 parts of defoaming agent, 1 part of water-based color paste, 8 parts of water; The preparation method of the composite rock slice comprises the following steps Step 1: Evenly disperse the formula and stir it into slurry, and evenly apply the slurry on the drying line base belt. The drying line base belt passes through a hot air circulation oven with a drying temperature of 110 degrees and a wind speed of 1.5m / s. The thickness of the coating after drying is controlled at 460um. The coating is peeled off by a brush roller with a speed of 250 rpm. Step 2: The dried coating layer is crushed by a crusher and then sieved by a screening machine to obtain 3mm flakes, which are packaged according to color and size. Step 3: Place the sheets in polyethylene plastic bags, and then place the polyethylene plastic bags in corrugated boxes for shipment. Example 3
[0022] 45 parts of elastic acrylic resin ethyl ester, 35 parts of calcium carbonate powder, 5 parts of titanium dioxide, 0.3 parts of dispersant, 0.3 parts of wetting agent, 0.3 parts of isocyanate, 4 parts of amino silicone oil, 0.2 parts of polyethylene wax, 0.2 parts of alkali swelling thickener, 0.3 parts of nonionic antistatic agent, 0.5 parts of defoaming agent, 1 part of water-based color paste, 8 parts of water; The preparation method of the composite rock slice comprises the following steps Step 1: Evenly disperse the formula and stir it into slurry, and evenly apply the slurry on the drying line base belt. The drying line base belt passes through a hot air circulation oven with a drying temperature of 120 degrees and a wind speed of -2m / s. The thickness of the coating after drying is controlled at 60um. The coating is peeled off by a brush roller with a speed of 280 rpm. Step 2: The dried coating layer is crushed by a crusher and then sieved by a screening machine to obtain 6mm flakes, which are packaged according to color and size. Step 3: Place the sheets in polyethylene plastic bags, and then place the polyethylene plastic bags in corrugated boxes for shipment. Example 4
[0023] 35 parts of elastic methyl acrylate resin, 20 parts of kaolin, 25 parts of calcium carbonate powder, 5 parts of titanium dioxide, 0.3 parts of dispersant, 0.3 parts of wetting agent, 0.1 parts of silane coupling agent, 2 parts of methyl silicone oil, 0.005 parts of hydroxyethyl cellulose, 0.2 parts of anionic antistatic agent, 0.5 parts of defoaming agent, 0.1 parts of water-based color paste, 11.495 parts of water; The preparation method of the composite rock slice comprises the following steps Step 1: Evenly disperse the formula and stir it into slurry, and evenly apply the slurry on the drying line base belt. The drying line base belt passes through a hot air circulation oven with a drying temperature of 110 degrees and a wind speed of 1.5m / s. The thickness of the coating after drying is controlled at 60um. The coating is peeled off by a brush roller with a speed of 260 rpm. Step 2: The dried coating layer is crushed by a crusher and then sieved by a screening machine to obtain 8mm flakes, which are packaged according to color and size. Step 3: Place the sheets in polyethylene plastic bags, and then place the polyethylene plastic bags in corrugated boxes for shipment. Example 5
[0024] 40 parts of elastic acrylic resin n-butyl grease, 10 parts of talc, 25 parts of light calcium carbonate powder, 10 parts of titanium dioxide, 0.3 parts of dispersant, 0.3 parts of wetting agent, 0.2 parts of polyamine, 0.2 parts of polyethylene wax, 0.2 parts of alkali swelling thickener, 0.5 parts of defoaming agent, 1 part of water-based color paste, 12 parts of water; The preparation method of the composite rock slice comprises the following steps Step 1: Evenly disperse the formula and stir it into slurry, and evenly apply the slurry on the drying line base belt. The drying line base belt passes through a hot air circulation oven with a drying temperature of 120 degrees and a wind speed of 2m / s. The thickness of the coating after drying is controlled at 70um. The coating is peeled off by a brush roller with a speed of 200 rpm. Step 2: The dried coating layer is crushed by a crusher and then sieved by a screening machine to obtain 7mm flakes, which are packaged according to color and size. Step 3: Place the sheets in polyethylene plastic bags, and then place the polyethylene plastic bags in corrugated boxes for shipment. Example 6
[0025] 45 parts of elastic acrylic resin ethyl ester, 35 parts of calcium carbonate powder, 5 parts of titanium dioxide, 0.3 parts of dispersant, 0.3 parts of wetting agent, 4 parts of amino silicone oil, 0.2 parts of polyethylene wax, 0.2 parts of alkali swelling thickener, 0.1 parts of nonionic antistatic agent, 0.5 parts of defoaming agent, 1 part of water-based color paste, 8.3 parts of water; The preparation method of the composite rock slice comprises the following steps Step 1: Evenly disperse the formula and stir it into slurry, and evenly apply the slurry on the drying line base belt. The drying line base belt passes through a hot air circulation oven with a drying temperature of 120 degrees and a wind speed of 2m / s. The thickness of the coating after drying is controlled at 70um. The coating is peeled off by a brush roller with a speed of 230 rpm. Step 2: The dried coating layer is crushed by a crusher and then sieved by a screening machine to obtain 9mm flakes, which are packaged according to color and size. Step 3: Place the sheets in polyethylene plastic bags, and then place the polyethylene plastic bags in corrugated boxes for shipment.
[0026] Performance test comparison 1. Anti-blocking properties: 4 samples were stacked, regardless of front or back, and placed in an oven at (40 + 2)°C for 2 hours. After the test, the samples were manually separated and observed for adhesion, with a classification of a) no adhesion, b) partial adhesion, and c) complete adhesion. 2. Flexibility: Select a specimen with a diameter greater than 3mm, fold it 180 degrees between your thumb and index finger, and immediately observe the bend. If two of the three specimens have no cracks or breakage, the flexibility is considered qualified. a) All specimens have no cracks, b) 2 specimens have no cracks, c) 1 or 0 specimens have no cracks; 3. Peelability: After the brush roller rotates and scrapes, there is no residual rock flakes on the drying line base belt. A: no residue, B: less than 3% residue, C: more than 3% residue; 4. Mechanical stirring stability: 100g of rock flakes were added to 200g of water in a 500ml container and stirred at 600 rpm in a small laboratory disperser for 20 minutes. The flakes were observed to see if they became smaller and if the water became turbid. a: No significant decrease in size and no significant turbidity in the water. b: Slight decrease in size and slight turbidity in the water. c: Change in size and turbidity in the water.
[0027] Those skilled in the art will appreciate that the embodiments of the present invention are intended to be illustrative only and are not intended to limit the present invention. The objectives of the present invention have been fully and effectively achieved. The functional and structural principles of the present invention have been demonstrated and illustrated in the embodiments. Any variations or modifications may be made to the embodiments of the present invention without departing from the principles described.
Claims
1. Composite rock slices, characterized by: Its raw materials include the following components in parts by weight: 25-40 parts of high elasticity and low tack resin; Dispersant 0.1-0.5 parts; Wetting agent 0.1-0.5 parts; Coupling agent 0.02-0.1 parts; 0.05-5 parts of release agent; Anti-adhesive agent 0.01-0.1 part; Thickener 0.1 part -1 part; Filling powder 50-60 parts; 0.1-2 parts of water-based color paste; 5-15 parts water.
2. The composite rock slice according to claim 1, characterized in that: The high elasticity and low tack resin refers to an acrylic emulsion, which is a type of acrylic emulsion with a micro-crosslinked structure formed by adding an appropriate amount of soft monomer to lower the Tg, i.e., the glass transition temperature, and utilizing the interaction of the special functional groups carried by the added functional monomers or oligomers to form ether bonds, bonds or amide groups, or forming CC bonds of the macromolecular chain through the addition action between double bonds.
3. The composite rock slice according to claim 1, characterized in that: The coupling agent is one or more of methyl silicate, silane coupling agent, isocyanate and polyamine.
4. The composite rock slice according to claim 1, characterized in that: The demoulding agent is one or more of methyl silicone oil, hydroxy silicone oil, phenyl silicone oil, amino silicone oil, mineral oil and alkyl oil.
5. The composite rock slice according to claim 1, characterized in that: The antistatic agent is a complex composed of a quaternary ammonium salt cationic surfactant and a nonionic surfactant.
6. The composite rock slice according to claim 1, characterized in that: The anti-sticking agent is one or more combinations of polytetrafluoroethylene micropowder, polyethylene wax, polypropylene wax and polyamide wax.
7. The composite rock slice according to claim 1, characterized in that: The wetting agent is one or more of anionic wetting agents and nonionic wetting agents.
8. The composite rock slice according to claim 1, characterized in that: The thickener is one or more of hydroxyethyl cellulose, alkali-soluble thickener, associative thickener, and polyurethane thickener.
9. The method for preparing the composite rock slice according to claim 1, characterized in that: Includes the following steps Step 1: Evenly disperse the formula and stir it into slurry, then evenly apply the slurry on the drying line base belt. The drying line base belt passes through a hot air circulation oven and is peeled off by a brush roller. Step 2: The dried coating layer is crushed by a crusher and then sieved by a screening machine to obtain flakes with a size of 1-10mm, which are packaged according to color and size. Step 3: Place the sheets in polyethylene plastic bags, and then place the polyethylene plastic bags in corrugated boxes for shipment.
10. The method for preparing a composite rock slice according to claim 1, characterized in that: The drying temperature is 100-120 degrees, the wind speed is 0.5-2m / s, the thickness of the coating after drying is controlled at 40-70um, and the speed of the brush roller is 200-300 rpm.
Citation Information
Patent Citations
Anti-adhesion ultrathin rock slice facilitating demolding and preparation process thereof
CN110819155A